2012
DOI: 10.1021/jf302285k
|View full text |Cite
|
Sign up to set email alerts
|

2,4,5-TMBA, a Natural Inhibitor of Cyclooxygenase-2, Suppresses Adipogenesis and Promotes Lipolysis in 3T3-L1 Adipocytes

Abstract: Obesity is a global health problem. Because of the high costs and side effects of obesity-treatment drugs, the potential of natural products as alternatives for treating obesity is under exploration. 2,4,5-Trimethoxybenzaldehyde (2,4,5-TMBA) present in plant roots, seeds, and leaves was reported to be a significant inhibitor of cyclooxygenase-2 (COX-2) activity at the concentration of 100 μg/mL. Because COX-2 is associated with differentiation of preadipocytes, the murine 3T3-L1 cells were cultured with 100 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The hallmark of adipocyte differentiation is the formation and enlargement of intracellular lipid droplets [20]. In this study, the extract of three herbs milkvetch root, salviae miltiorrhizae and mulberry as key components of MTF effectively decreased the accumulation of lipids in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 76%
“…The hallmark of adipocyte differentiation is the formation and enlargement of intracellular lipid droplets [20]. In this study, the extract of three herbs milkvetch root, salviae miltiorrhizae and mulberry as key components of MTF effectively decreased the accumulation of lipids in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 76%
“…Twenty-four hours after seeding, the cells were treated with LPS (1 μg/mL) and various concentrations of test samples for another 24 h. At the end of the treatment, medium was removed and the cells were cultured with new DMEM containing MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) at a final concentration of 0.5 mg/mL for 4 h. The purple formazan was dissolved by DMSO, and the absorbance at 570 nm was taken. The absorbance is proportional to the viability of cells …”
Section: Methodsmentioning
confidence: 99%
“…The absorbance is proportional to the viability of cells. 47 Measurement of Pro-inflammatory Mediators. After the cells were treated with various concentrations of test samples for 1 h and LPS for 6 h, the culture medium was collected for the measurement of IL-1β and TNF-α by using ELISA kits purchased from Biolegend (San Diego, CA, USA).…”
Section: T H Imentioning
confidence: 99%
“…Previously, we showed that 2,4,5-TMBA suppresses the differentiation of preadipocytes . In this study, preadipocytes were co-cultured with 2,4,5-TMBA specifically at post-induction days 0–2, 2–4, 4–6, or 6–8 only to further figure out the stages that are critically affected by 2,4,5-TMBA during adipogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…COX-2 not only plays a role in the inflammatory process but is also involved in the modulation of adipogenesis. , In our previous study, 3T3-L1 preadipocytes and adipocytes were treated with 0.5 mM 2,4,5-TMBA to explore its effect on adipogenesis and lipolysis. The results showed that 2,4,5-TMBA suppressed differentiation of preadipocyts into adipocytes and enhanced lipolysis in mature adipocytes …”
Section: Introductionmentioning
confidence: 99%